Evaluation of Novel Therapeutic Approach and Surgical Management of Closed Cervix Pyometra in Bitches - Gupta, Chhavi; Krishnakum, K; Malmarugan, S; Chellapandian, M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted in the twenty-eight number of bitches aged between 2 to 6 years presented to SAC-OP-OG unit of Madras Veterinary College Teaching Hospital with a history of inappetence, lethargy, polyuria, polydipsia and distended abdomen which was further confirmed as pyometra by radiography and ultrasound examination. Further, the bitches were divided equally into group I and II. Group I (n=14) was treated with Tab. Mifepristone @ 2.5 mg/kg b.wt. per OS, Tab. Cabergoline @ 5 µg/kg b.wt. per OS and Tab. Misoprostol @ 100 µg per vaginum for 7 to 14 days. Group II (n=14) bitches directly underwent ovariohysterectomy. The assessment of uterine distention was performed by follow-up ultrasonography on day 7, 14, 21 and 28. The blood samples were collected on day 0 (before administering treatment) and on day 7, 14 and 21 in both groups for haemato-biochemical examination. In Group I, 78.57% and 63.63% of cases responded and conceived, respectively, in next cycle, while 9.09% cases had recurrence of pyometra. The altered haemato-biochemical indices in Group I and II were reversed between 14 to 21 and 7 to 10 days, respectively. The study concluded that the physiological and haemato-biochemical reversal is delayed in Group I with ovariohysterectomy, but mifepristone and cabergoline used in Group I prove to be safe and efficient therapeutic protocol for management of closed pyometra and restoring the breeding ability in young bitches.